2019
DOI: 10.1002/ejsp.2579
|View full text |Cite
|
Sign up to set email alerts
|

“Sad day for the UK”: The linking of debates about settling refugee children in the UK with Brexit on an anti‐immigrant news website

Abstract: This article uniquely demonstrates how UK debates about supporting child refugees during the “refugee crisis” came to be used as support for leaving the European Union (EU). The research question “how did users of a news website respond to a report about the UK government's decision to allow child refugees into the UK?” is addressed with a rigorous discursive analysis of an internet discussion forum on the anti‐immigrant website MailOnline consisting of 2,014 unique posts, with a reach of 30 million viewers. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 36 publications
(93 reference statements)
0
8
0
Order By: Relevance
“…Nevertheless, anti‐refugee arguments were still possible, as the findings demonstrate. For example, Goodman and Narang () showed how support for child refugees was undermined by the ongoing suggestion that they were really adults posing as children. In addition, they showed that in the UK, the refugee crisis was used to justify voting to leave the European Union.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, anti‐refugee arguments were still possible, as the findings demonstrate. For example, Goodman and Narang () showed how support for child refugees was undermined by the ongoing suggestion that they were really adults posing as children. In addition, they showed that in the UK, the refugee crisis was used to justify voting to leave the European Union.…”
Section: Introductionmentioning
confidence: 99%
“…How the European Union (EU) should respond to the crisis has been controversial and has itself been considered a crisis for the Union. The UK's decision to leave the EU has been shown to be influenced by the refugee crisis and general opposition to migration (Goodman & Narang, ).…”
Section: Introductionmentioning
confidence: 99%
“…On the anti-refugee side, populist parties argue that society is in decline and that limiting immigration is necessary to protect it. For example, Donald Trump and Brexit supporters both argued that immigration should be restricted in order to restore society (Edwards, 2018;Goodman & Narang, 2019). On the pro-refugee side, critiques of (neoliberal) contemporary society are accompanied by calls for equality and provision for those in need, including refugees (Boersma et al, 2019).…”
mentioning
confidence: 99%
“…In one image, a bearded dark‐skinned man is depicted with a bubble saying ‘I’m only seventeen’ (Appendix S1: Image 8), resonating with the storyteller’s line: ‘Disregarding resources and safety, the leaders welcomed a flood of people, including those who never really needed asylum’ (01:39–01:49). The text is a sarcastic intertextual clue referring to the anti‐immigrant debate about the age of asylum seekers implying that some adult refugees are pretending to be children (Goodman & Narang, 2019). Moreover, differentiating between ‘real’ and ‘false’ refugees allows criticism of immigration while maintaining a reasonable and sympathetic approach to ‘genuine’ asylum seekers (Lynn & Lea, 2003; Sakki & Pettersson, 2018).…”
Section: Methodsmentioning
confidence: 99%